The Influence of Job Satisfaction and Organizational Commitment on Performance by Using Person-Organization Fit as Moderating Role (Study: PT. HM Sampoerna Putra of Central Java and DIY) - Manik Suryandaru Raka Timur, 1242020115; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research investigates the effect of job satisfaction, organizational commitment on employee performance by using Person-Organization Fit as moderating role in PT. HM Putra Sampoerna of Central Java and DIY. The respondent of this research is the employees of PT. HM Sampoerna Putra of Central Java and DIY those are of 120 employees consist of 5-10 years job tenure are 69 employees (57,5%), 11-15 years job tenure are 19 employees (15,8%) and more than 15 years job tenure are 5 employees (4,2%). This research uses proportionate random sampling and multiple linier regression by using SPSS. The result shows that Job Satisfaction and Organizational Commitment positively and significantly influence Employee Performance, and Person-Organization Fit as Moderating variable moderates the relationship between Job Satisfaction and Organizational Commitment on Employee Performance. This research managerial implication is the salary adjustment to full fill economic needs, and feel satisfy to the leader support which can increase the employee performance. Managerial must keep and improve the salary adjustment system, leader support to increase the employee performance in PT. HM Sampoerna Putra of Central Java and DIY. khey Word: Job Satisfaction, Organizational Commitment, Performance and Person-Organization Fit.